Recent advances in therapeutic bronchoscopy1 (Swiss Medical Weekly, 2012)
Therapeutic bronchoscopy has come a long way from removal of foreign bodies to minimally invasive techniques in management of diseases like lung cancer, chronic obstructive pulmonary disease and asthma. This article discusses the exciting new techniques of therapeutic bronchoscopy namely; bronchoscopic lung volume reduction, bronchial thermoplasty, radiofrequency ablation, and use of fiducial markers in external beam irradiation.